NET GRAF CALCULATION METHOD FOR JOB COMPLETION CONSIDERING OF RESOURSES AVAILABALE - G. V. Golovchenko; M. I. Rebezova (Научный вестник МГТУ ГА)
The research considers the activity based network of routines performed by the integrated servicing crews at the airport. The known algorithms for critical path claiming suppose that the activity duration is given and the beginning of any activity is determined. However, the beginning of the activity also depends on the presence of the necessary resources for the given period of time.The formal statement of the problem is described. For the solution of the problem the well-known algorithm for constructing the tree of the shortest paths of the network graph is used. Herewith we suppose, that activity durations are known and resources are sufficient in order to start each activity at the right time. Further, this algorithm is modified inorder to take into account available resources. The special two-dimensional matrix with rows showing resource units andcolumns denoting the equally separated time intervals is used to demonstrate the resources state. The numerical method is proposed for solving the optimization problem. The method is implemented using the Mathcad computing environment and validated by specific examples.The method is implemented as a complex automated solution for operational management of airport services in the critical situations.